Implementasi Model Pembelajaran Card Sort Pada Mata Pelajaran Akidah Akhlak Kelas IV MI Al-Islam Desa Pranggang Kecamatan Plosoklaten Kabupaten Kediri - Uswatun Hasanah; Siti Wahyuni (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
Learning by using card sort can be through the principle of apperception, the principle of motivation, the principle of self-employment and the principle of regular repetition. With card sort students are more motivated in learning so they are able to understand lessons and improve learning outcomes in accordance with the expected completeness standards. This research method is qualitative. As with the direction of qualitative research, the collected data is analyzed with the provision of intellectual weapons in the form of theory as presented in chapter II to obtain various interpretative descriptions in accordance with the rules of scientific research that are logical and rational. The results of this study are: (1) The application of the Card Sort Method to grade IV students in akidah akhak subjects in MI Al-Islam Desa Pranggang Kecamatan Plosoklaten Kabupaten Kediri, the teacher gives an index card containing the material of moral study. The more students there are, the more card pairs there are. (2) Changes in student learning outcomes after being taught using class IV card sort method in akidah akhlak subjects in MI Al-Islam Desa Pranggang Kecamatan Plosoklaten Kabupaten Kediri, are the cognitive test results of students getting an average score of 84.14, on the affective aspects of students have a sense of faith and devotion to God in psychomotor students implementing Islamic religious teachings in daily life so as to shape the knowledge, attitudes and skills of all students here according to the target, which is to integrate the cognitive, affective and psychomotor domains in all learning activities. And the students' response to this learning method is very good because of students like the method of learning card sort